Nature as Nation: Cultural Meanings of Biodiversity on Sri Lankan Currency - Kirubalini, S.; Jasotharan, R. (University of Jaffna, Sri Lanka, 2026)
This paper examines the representation of biodiversity on Sri Lankan currency and its role in constructing national identity, cultural meaning, and awareness of natural heritage. Following Sri Lanka’s transition to a republic with the 1972 Constitution, artist Laki Senanayake was commissioned in the late 1970s to design banknotes featuring exclusively endemic flora and fauna. Seven currency notes are unique, as no other Sri Lankan currency has been dedicated entirely to biodiversity, although many subsequent notes include individual endemic or endangered species as part of their design. The study addresses three key questions: How is biodiversity depicted on these currency notes? What were the discourses behind the inclusion of flora and fauna? And how does the selective representation of biodiversity communicate national identity to domestic audiences and tourists? The objectives are to analyze visual representations on these seven banknotes, explore their role in articulating a cohesive sense of Sri Lankanness, and examine their alignment with global conservation and heritage frameworks. A qualitative methodology is employed, combining iconographic and visual analysis with contextual interpretation, applying Benedict Anderson’s theory of the imagined communities. Findings indicate that these currency notes construct Sri Lanka as biologically rich and culturally unified, marking a deliberate shift from political portraiture to neutral natural symbols. While biodiversity imagery communicates subtle environmental and heritage values and enhances the nation’s appeal to tourists, its selective inclusion—limited to only seven notes—shows that nature was never the dominant theme in currency design compared to cultural heritage imagery. This selective representation underscores the need for further research into how environmental elements are prioritized or marginalized in everyday cultural objects and how they contribute to public understanding of biodiversity and national identity.
Keywords: Biodiversity; National identity; Sri Lankan currency; Cultural representation; Heritage